MARKET SURVEY ON TRADITIONAL MEDICINE OF THE THIRD MONTH FAIR IN DALI PREFECTURE IN YUNNAN PROVINCE, SOUTH WEST CHINA - Zhang, Dequan; Duan, Lizhen; Zhou, Nong (African Journal of Traditional, Complementary and Alternative Medicines, 2014)
Background: The Third Month Fair in Dali is a historical festival and fair. The market of traditional medicine (TM) is one of the main parts in the fair, which has important influence on local and peripheral people. Materials and Methods: In this study, approaches of ethnobotany, pharmacognosy, and participatory rural appraisal were used in market survey. Twenty-six druggists were selected randomly as informants and their TMs were recorded. Results: As a result, 427 TMs were recorded including 362 plant medicines, 33 animal medicines, 13 mineral medicines and 19 unidentified medicines. Xinyi, Shanza and Gancao were the most popular medicines due to their popular usages, whereas Sanqi, Tianma and Renshen were relatively fewer in this investigation probably owing to high price and limited output. The plant medicines were from medicinal plants of 117 families belonged to Angiosperm, Gymnospermae, Pteridophyta, Bryophyta, Lichenes and Fungi. Asteraceae, Apiaceae and Fabaceae provided the maximum numbers of TMs successively. Moreover, these TMs were mainly from the cultivated especially familiar TMs, which reflected significant progress in utilization and conservation of medicinal resource in China. Conclusion: Medicinal market in the Third Month Fair is the most important traditional bazaar in Yunnan province. This study systematically surveyed TMs in the fair for the first time, analyzing and revealing resource compositions and current market situations. These newly gathered data provided precious information for development of medicine cultivation, resource protection and market management as well as further pharmacognostical, pharmacological and clinical researches.